Transcriptome analysis of iron over‐accumulating Arabidopsis genotypes uncover putative novel regulators of systemic and retrograde signaling - Louis Grillet; En‐Jung Hsieh; Wolfgang Schmidt (The Plant Genome, 2024)
Abstract On account of its competence to accept and donate electrons, iron (Fe) is an essential element across all forms of life, including plants. Maintaining Fe homeostasis requires precise orchestration of its uptake, trafficking, and translocation in order to meet the demand for Fe sinks such as plastids. Plants harboring defects in the systemic Fe transporter OPT3 (OLIGOPEPTIDE TRANSPORTER 3) display constitutive Fe deficiency responses and accumulate toxic levels of Fe in their leaves. Similarly, ectopic expression of IRONMAN (IMA) genes, encoding a family of phloem‐localized signaling peptides, triggers the uptake and accumulation of Fe by inhibiting the putative Fe sensor BRUTUS. This study aims at elucidating the mechanisms operating between OPT3‐mediated systemic Fe transport, activation of IMA genes in the phloem, and activation of Fe uptake in the root epidermis. Transcriptional profiling of opt3‐2 mutant and IMA1/IMA3 overexpressing (IMA Ox) lines uncovered a small subset of genes that were consistently differentially expressed across all three genotypes and Fe‐deficient control plants, constituting potential novel regulators of cellular Fe homeostasis. In particular, expression of the the F‐box protein At1g73120 was robustly induced in all genotypes, suggesting a putative function in the posttranslational regulation of cellular Fe homeostasis. As further constituents of this module, two plastid‐encoded loci that putatively produce transfer ribonucleic acid (tRNA)‐derived small ribonucleic acids are possibly involved in retrograde control of root Fe uptake.